FREQUENCY OF COMMON UROGENITAL ANOMALIES IN PATIENTS PRESENTING WITH HYPOSPADIAS - Ahmad, Shahzad; Ali, Qazi Amjad; khan, Nasir hayat; khan, Mansoor (Khyber Journal of Medical Sciences, 2022)
INTRODUCTION:Hypospadias is a congenital anomaly in the development of the urethra, in which the urethralmeatus is abnormally positioned with a ventral opening in the surface of the penis. Early diagnosis and treatment may provide a quality of life similar to that of healthy children with a lower financial burden for society.Once we got the actual prevalence of such anomalies in this part of world once, because no such study available locally. OBJECTIVE:To determine the frequency of common urogenital anomalies in patients presenting with hypospadias. METHODOLOGY: This study was carried out at plastic and reconstructive unit Hayatabad Medical complex Peshawar. Study design was descriptive cross-sectional study and duration of study was one year from 1st July 2019 to 30th June 2020. The sample size was 88 using 95% confidence level, proportion of 15% 8 of inguinal hernia with the margin of error of 7.5% under WHO formula for sample size calculation. All male patients of age 3-12 years and below presenting with hypospadias were included. After detailed clinical history and physical examination abdominal ultrasound was done for all hypospadias patients to confirm the urogenital anomalies by expert sonologist having five years post fellowship experience. The collected data of the study was organized and analysed with statistical package for social sciences (SPSS version 17). RESULTS:In this study mean age was 7 years ± 8.12.Most common urogenital anomalies were inguinal hernia 37%, ambiguous genitalia 15%, undescended testes 30%. CONCLUSION:Most common urogenital anomalies were inguinal hernia 37%, ambiguous genitalia 15%, undescended testes 30%